Hybrid Contract Analysis On Sharia Safe Deposit Box Service Products - Eka Wahyuningrum; Ismail Yahya (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This study aims to determine the hybrid contract for sharia safe deposit box service products at Bank Bukopin Syariah Solo Branch Office. This research is a type of qualitative research that is a field case study. The research approach method used in this study is qualitative method. Qualitative research methods are research methods that use methods, steps, and procedures that involve more data and information obtained through resource persons as subjects who can devote answers to get a general picture of a matter under study. Data collection techniques are obtained by observation, interviews, and documentation. Based on the results of the study, it was concluded that Bank Bukopin Syariah Solo applies ijarah contract as the main contract in safe deposit box service products. In addition to ijarah contracts, there are other contracts that are used as supporting contracts. Hybrid contracts contained in safe deposit box rental are ijarah, rahn, wadi'ah yad amanah and wakalah.